Pencegahan Stunting dengan Inovasi Teknologi berupa Modifikasi Timbangan Digital Terkoneksi Android - Sudarsono, Bambang; Sukesi, Tri Wahyuni; Tentama, Fatwa; Mutmainah, Nur Fitri; Yuliansyah, Herman; Mulasari, Surahma Asti; Nafiati, Lu’lu’; Sulistyawati, Sulistyawati; Ghozali, Fanani Arief (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Stunting is a problem that has a negative impact on society and can last for a long time. This community service program aims to increase the knowledge and skills of partner communities in preventing stunting by using innovative technology called the